2004
DOI: 10.1177/097318490400100203
|View full text |Cite
|
Sign up to set email alerts
|

Civics, Citizens and Human Rights: Civics Discourse in India

Abstract: This paper examines the discourses, visions and ideologies that have shaped the ideas about civics, citizen and human rights education in India over the last one-and-a-half decades. It tries to assess the congruence of the aims of human rights education with the existing understanding andpractice of civics in India.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 4 publications
0
8
0
Order By: Relevance
“…For this, the chapters, especially those in the social science subjects, are also organised and structured to reflect this approach, with section headings in the form of questions, the chapters full of political cartoons, photo essays, in-text and end-text questions. These news books are a contrast to the previous books which as Madan (2003) and Jain (2004) argue familiarise the students about the political system, the rights and duties of the citizens in an ideal way. The old books tend to engage with the issues of caste, gender and class as abstract entities.…”
Section: 'Caste' In the National Curriculummentioning
confidence: 96%
“…For this, the chapters, especially those in the social science subjects, are also organised and structured to reflect this approach, with section headings in the form of questions, the chapters full of political cartoons, photo essays, in-text and end-text questions. These news books are a contrast to the previous books which as Madan (2003) and Jain (2004) argue familiarise the students about the political system, the rights and duties of the citizens in an ideal way. The old books tend to engage with the issues of caste, gender and class as abstract entities.…”
Section: 'Caste' In the National Curriculummentioning
confidence: 96%
“…16 Between 1997 (when I was researching textbooks in Rajasthan) and (when the NCERT published its textbooks), there occurred some major shifts in the understanding of the discipline of Civics in school textbooks. One major shift was to move away from the colonially handed down notion of subjects/citizen (Jain, 2004(Jain, , 2005 towards a more engaged and agency-laden people. My own research (George, 2007) identified the need to move away from prescriptive and information-based textbooks, 17 to a more narrative methodology which children could engage in discussions and critique.…”
Section: Experiences Of Ncert Textbook Writingmentioning
confidence: 99%
“…Scholars (Batra, 2015;Jain, 2004), however, have drawn attention to the limitations of this kind of a concerted attempt to portray 'a united nation' (Batra, 2015, p. 40) through school curricula. According to Batra, such attempts definitely contributed towards nation-building by encouraging the common people to 'take pride in the country's pluralistic heritage' (ibid.).…”
Section: Curricular Shifts In the Indian Contextmentioning
confidence: 99%